Ekonomiczna kalkulacja? Ołtarze iluzjonistyczne XVIII wieku na terenie Słowacji - Kolbiarz Chmelinová, Katarína (TECHNE. Seria Nowa, 2018)
The majority of the 18th century altars in Central Europe are objects made of polychromed wood, stucco, or stone. There are, however, other altars whose retabula – as a whole or predominantly – take the form of a wall painting. The basis for these works is a spatial and material illusion, which imitates the presence of a real reredos within the painting, and in some cases even the imagined space around it. The beginnings of the monumental, architecturally illusionistic murals in Central European art are undoubtedly connected with the Viennese activity of Andrea Pozzo in the early 18th century, and his famous treatise entitled Perspectiva pictorum et architectorum. The principia of new formal achievements, instilled in the Habsburg capital, subsequently radiated ontowall painting, including the illusionistic altars of various kinds and constructed at different timeswithin neighbouring countries. In Slovakia, painted, illusionistic altars have not so far been the subject of systematic research. Over the centuries, numerous such altars have either been destroyed or preserved in a truly terrible condition. Thus, this article is the first to present a summary view on such types of works in the region, with the elaboration of a new, basic, chronological and typological order. The initial part of the article is devoted to the presentation of the fewdirect reflections of Pozzo’s works, which were created in the first half of the 18thcentury. The review begins with the works by Christoph Tausch (Banska Štiavnica), Pozzo’s protegeand assistant, which are known only from archival citations and references. The next stage of the development of illusionistic altars, dated to the mid-18thcentury, is represented by a set of six wall paintings from temples in the Banska Štiavnica Calvary between 1744 and 1751. These works, referring to Pozzo’s achievements and the Viennese art, were created by Anton Schmidt (1713-1773), a graduate of a local art academy. On the one hand, the paintings had been ordered from a leading regional artist, and on the other hand, the applied technique entailed a pragmatic reduction in time, costs, and the occupied space within the temples. Broadly speaking, however, illusionistic altars had not gained popularity by the first half of the century, unlike in Austria, Bohemia and Silesia, and they were created in an updated form, including the latest artistic trends of the time. The apogee of the whole process dates to the last three decades of the 18thcentury and includesthe works that cultivated both solutions representinglate Baroque and Rococo styles, and the features of early Classicism. Model examples are the painted decorations within the presbytery of the church of the Pauline Fathers in Šamorin from 1778, initialled with the monogram of F.S. (and made in accordance with an older model, patterned on the work by Paul Heineken), and a series of illusionistically painted retabulain the Premonstratensian church in Košice, created in the late 18th century by Erasmus Schrott (1755-1804), who was closely linked to Viennese circles. A further part of the article discusses a group of miscellaneous works – at times simpler and cheaper – which graced a series of parish churches. The introduction,in the territories of today’s Slovakia, and the subsequent growth in popularity of a particular type of altar retabulum, created by means of a wall-painting technique (mainly fresco-secco) dates to the 18th century, with its apogee in the final three decades of the century. Typologically, it was dominated by tectonic reredoses, with various degrees of complexity – from simpler variants of aediculae, through a pillared niche and a colonnade, to Apsisaltar. Sometimes, these are also imitations of canopy-type altars or altars with an applied motif of a canopy in the central axis or in the topping. Occasionally, there are also imaginations of an illusionistically painted ceremonial drapery in the background. In the case of illusionistic altars, just like for the remaining types of architectural wall painting, an important role at the designing stage was played by architectonic treatises and patterns. In the said territory, particular popularity was enjoyed by Andrea Pozzo’s treatise, with others including the works by Heineken, Galli-Bibiena and Schubler. It must also be stated that after the second half of the 18th century, no major changes were implemented, and the older patterns and models, already rooted in the tradition, were chiefly updated by means of more modern ornaments. It was not until the last three decades of the century that the post-Pozzo tradition began to recede at the expense of simpler structures which complied more aptly with the spirit of the incoming Classicism. In the entirety of the illusionistic painting – both decorations of vaults and retabula – an important role was played by the Viennese centre of art, and not only in reference to the territories of today’s Slovakia, but also to Central and East-Central Europe. A significant number of wall-painting authors remain unknown,and as far as the issue of orders is concerned, it is impossible to ignore the fact that these works were most popular among the representatives of the Roman Catholic Church. It is also quite obvious that painted altars were more inexpensive, less time-consuming to complete, and easier to undergo modifications in due course. Illusionistic altars, created in the northern part of the former Kingdom of Hungary in the 18th century,had numerous imitations in the subsequent century. The last part of the paper presents the continuation of the tradition, including historicising works illustrated with an example of the work of the Franciscan painter Konrad Švestka (1833-1907).